Literature Study: Implementation of Self Organized Learning Environments (SOLE) - Abu, St. Hayatun Nur; Gustina, Gustina; Bundu, Patta; Haling, Abd. (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
The implemented learning process in the classroom effectively can enhance the quality of education, and students' abilities in terms of knowledge, attitudes, and skills will be achieved as expected in the curriculum. Learning is planned and organized in such a way that it can influence and assist students' learning activities. One of the learning models in line with the curriculum is the SOLE Model; this learning model helps teachers stimulate students' curiosity from within themselves by organizing student-centred learning. This research aims to determine the implementation of the SOLE learning model. The research method uses a qualitative approach to obtain relevant data and data sources. Data collection is done through a literature study from relevant journals. The research results show that the SOLE learning model can be used as an innovation in learning to improve students' learning activities, motivation, understanding of the material, learning autonomy, self-directed learning, and creativity, ultimately leading to improved student learning outcomes.